(untitled) (Web of Teachers: Inderscience Research, 2025)
This article examines an information and methodological support system designed to develop the professional competence of future foreign language teachers. In the context of globalization and digitalization of education, enhancing professional competence becomes a key factor in successful pedagogical activity. Particular attention is paid to the integration of information technologies into the educational process and their impact on the quality of teacher training. The research results demonstrate that the use of this system contributes to improving the level of professional competence, enhancing methodological skills, and readiness for work in modern conditions. The article concludes with recommendations for the implementation of the system in educational institutions and outlines prospects for further research in this field.